Flag Of Defiance: The International Use of the Rhodesian Flag Following UDI. Issue 3 (3rd July 2019) - Berry, Bruce
Abstract: The international response to Rhodesia's Unilateral Declaration of Independence (UDI) was to proclaim the colony to be in a state of rebellion, the government in Salisbury to be illegal, and to request the United Nations to apply sanctions against the 'rebel regime'. The ensuing political impasse resulted in the need to promote a more distinctive national identity and the symbols to reflect this newfound independence. The first, and most obvious, change came with the adoption of a new national flag on the third anniversary of UDI on 11 November 1968. As the most visible symbol of post-UDI Rhodesia, the international use and display of the new flag became the subject of demonstration and controversy. This paper shows how the green and white Rhodesian flag came to highlight Rhodesia's contested statehood when flown outside the country during the UDI period. Rhodesia's new flag became a symbol of the country's defiance, and the emotion it evoked, and continues to evoke, causes controversy even to this day.